Vision Tech Enterprise : Eco Portable Charger / Nurul Atiqah Mohd Yusof ...[et al.] - Mohd Yusof, Nurul Atiqah; Eling, Nadia; Anon, Shirlyria; Mohamad Abu Bakar, Nurhazliza; Michael, Zita; Micheal Mira, Micsewell (2015)
Company which focuses on technology product in Malaysia. The product we are design is the Eco Portable Charger. Most electronic devices run on battery and sometimes one can barely find the time to recharge them. For people who enjoy an active lifestyle, they will find it difficult to keep their entertainment device charged while they are On- The-Go. Therefore the objectives of this product are to produce a device that converts human body motion into electrical energy and to create a working prototype to charge an entertainment device such as MP3 player. The device created can remedy the situation whereby no one will have to wait around to recharge their iPods and smart phones. In this era of technological advancement, m st people can hardly leave behind their electronic or entertainment devices such as MP3, mobile phone and tablets while they are performing their daily routine. In fact, some people even bring along their devices at all time with them. however, all of thee portable electronic gadgets actually operate On batteries and once their batteries runs out, the users are required to attach these devices to ,a other power source to recharge them. In accordance to the development of green technology, many researchers have been trying to utilize the renewable energy as a power source for the portable gadgets.